2020
DOI: 10.4236/ss.2020.1110032
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infections in Peptic Ulcer Perforations: A Retrospective Analysis in Two Referral Hospitals in Douala, Cameroon

Abstract: Background: Perforations are major complications of peptic ulcer disease and surgical emergencies with important mortality and morbidity. Helicobacter pylori (H. pylori) has been identified as one of the commonest factors associated with peptic ulcer disease. However, little is known about its implication in cases of perforations in Cameroon. We aimed to determine the frequency of Helicobacter pylori infections in cases of perforated peptic ulcers, describe clinical features and outcomes of these cases in Came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Moreover, studies showed that several virulence factors such as outer inflammatory protein (OipA), epithelial gene A1 (iceA1), babA2-gene positive (encodes BabA protein), duodenal ulcer promoting gene cluster (dupA cluster), vacA s1/m1 genotype, and cagA-gene positive expression are associated with peptic ulcer disease [61]. Our study showed that approximately 58% of patients with gastroduodenal perforation were infected with H. pylori, which is consistent with previously reported studies [62]. Patients afflicted with H. pylori should undergo treatment to eradicate infection and avoid its reoccurrence, hence averting the development of gastrointestinal diseases [2].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, studies showed that several virulence factors such as outer inflammatory protein (OipA), epithelial gene A1 (iceA1), babA2-gene positive (encodes BabA protein), duodenal ulcer promoting gene cluster (dupA cluster), vacA s1/m1 genotype, and cagA-gene positive expression are associated with peptic ulcer disease [61]. Our study showed that approximately 58% of patients with gastroduodenal perforation were infected with H. pylori, which is consistent with previously reported studies [62]. Patients afflicted with H. pylori should undergo treatment to eradicate infection and avoid its reoccurrence, hence averting the development of gastrointestinal diseases [2].…”
Section: Discussionsupporting
confidence: 92%
“…Because it is frequently hard to identify the specific place of the perforation, it is typically referred to in studies as juxta pyloric or pyloro-duodenal. In their research, Mathur et al discovered a rise in the prevalence of pyloro-duodenal perforation [17][18] . For many years, people with a prolonged peptic ulcer history have been known to be more susceptible to develop an ulcer after perforation.…”
Section: Discussionmentioning
confidence: 99%